Né assassine né peccatrici. Identità e libertà delle donne oltre l’autodeterminazione - Vari, Autori (Il sogno della farfalla, 2009)
After having published, in the second number of 2008 of this journal, M. G. Gatti’s contribution to the debate held on 23.2.2008 in Rome at the Palazzo delle Esposizioni, we now propose a synthesis of the talks given by the other speakers (the journalist R. Armeni, the psychiatrist A. Homberg) the co-ordinator (L. Profeti) and the general debate. The meeting was inspired by the current controversy, very animated nowadays in Italy, on the interruption of pregnancies triggered off by pressures coming from the catholic world in strong opposition to the law which currently allows it. While Armeni highlights the socio-political aspects linked to the history of the women’s movement, other talks look carefully at the question of pregnancy and the beginning of life. The critical reflections made by A. Homberg on the sense of guilt inflicted on women who have had abortions find a basis in scientific evidence demonstrating that it is not possible to speak about human life in relation to a foetus, already proposed by M.G. Gatti and discussed further during the debate by, among others, M. Fagioli.